The casual vacancy [large type] - Rowling, J. K. (Little, Brown & Co., 2012)
When Barry Fairbrother dies in his early forties, the town of Pagford is left in shock and the empty seat left by Barry on the parish council soon becomes the catalyst for the biggest war the town has yet seen.